Surgical delay in appendicitis among children: the role of social vulnerability - Estefany, Villa-Aguilar; Karen, Marín-Morales; Citlali, Ayala-Galvan; Ailema, Gonzalez-Ortiz; Jose Francisco, Gonzalez-Zamora (Frontiers in Pediatrics, 2025)
BackgroundAppendicitis is the most common abdominal emergency in pediatrics and is suggested as a quality indicator for timely access to care in time-sensitive conditions. Despite advances in diagnostics, the incidence of complicated appendicitis (CA) remains high due to delays in pediatric surgical care, which can increase disease severity. Social vulnerability has been associated with surgical access, particularly in low- and middle-income populations. This study examines the relationship between surgical delay and social determinants of complicated appendicitis in children without social security in the Metropolitan Zone of México.MethodsThis retrospective cohort study was conducted in a pediatric public hospital. Consecutive cases from 2018 to 2021 with confirmed appendicitis diagnoses were included. The primary outcome variable was the type of appendicitis (acute/complicated), while two independent variables were the time of evolution (patient and hospital timing) and socioeconomic factors associated with social vulnerability. A logistic regression analysis assessed the relationship between appendicitis type and covariates.ResultsA total of 943 pediatric cases of appendicitis were included. Out of these, 62.67% presented CA, with a mean age 10 ± 4 years. 60.9% were well-nourished, and 16% had at least one comorbidity. Most subjects (76%) met at least two criteria for social vulnerability, and 74.7% of families held unskilled jobs. The median symptom-to-admission time was 2 days, with a median hospital-to-surgery time of 19.5 h (p25–p75). Prehospital delays affected 57.8% of cases (n = 545), and 39% (n = 365) experienced intrahospital delays. In the multivariable logistic regression, prehospital delay ≥48 h (OR 3.27, 95% CI 2.43–4.39) and children under 5 years (OR 1.76, 95% CI 1.09–2.84) were associated with higher odds of CA.ConclusionThe high frequency of CA in uninsured children at a public hospital is due to surgical delays of two or more days. Social vulnerabilities, as observed globally, hinder access to quality care. Thus, appendicitis should be recognized as both a medical and social issue, requiring a comprehensive approach that addresses social vulnerability.